Weekend admissions as an independent predictor of mortality: an analysis of Scottish hospital admissions - Handel, A; Patel, S; Skingsley, A; Bramley, K; Sobieski, R; Ramagopalan, S (BMJ Publishing Group, 2012)
OBJECTIVES: Weekend admissions have been shown to be associated with an increased risk of mortality compared with weekday admissions for many diagnoses. We analysed emergency department admissions within the Scottish National Health Service to investigate whether mortality is increased in case of weekend emergency department admissions. DESIGN: A cohort study. SETTING: Scotland National Health Service (NHS) emergency departments. PARTICIPANTS: 5 271 327 emergency department admissions between 1999 and 2009. We included all patients admitted via emergency departments recorded in the Scottish Morbidity Records (SMR01) in NHS, Scotland for whom complete demographic data were available. PRIMARY OUTCOME MEASURES: Death as recorded by the General Register Office (GRO). RESULTS: There was a significantly increased probability of death associated with a weekend emergency admission compared with admission on a weekday (unadjusted OR 1.27, 95% CI 1.26 to 1.28, p<0.0001; adjusted for year of admission, gender, age, deprivation quintile and number of comorbidities OR 1.42, 95% CI 1.40 to 1.43, p<0.0001). CONCLUSIONS: Despite a general reduction in mortality over the last 11 years, there is still a significant excess mortality associated with weekend emergency admissions. Further research should be undertaken to identify the precise mechanisms underlying this effect so that measures can be put in place to reduce patient mortality.